2002
DOI: 10.1038/418932a
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive change and the APOE ɛ4 allele

Abstract: There is a marked variation in whether people retain sufficient cognitive function to maintain their quality of life and independence in old age, even among those without dementia, so it would be valuable to identify the determinants of normal age-related cognitive change. We have retested non-demented 80-year-olds who were participants in the Scottish Mental Survey of 1932, and find that the variation in their non-pathological cognitive change from age 11 to 80 is related to their apolipoprotein E (APOE) geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
192
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(212 citation statements)
references
References 11 publications
15
192
4
1
Order By: Relevance
“…Despite the high heritability of intelligence, 12,28,37,38 the progress in the identification of loci consistently associated with variation in its normal range has thus far been limited. 15,17,[38][39][40][41][42] Exceptions are the apolipoprotein E (APOE) gene at older ages 43 and formin binding protein 1-like (FNBP1L), the latter having recently been shown to be associated with both childhood and adulthood intelligence. 15,17 The present approach utilizes the idea that the differentially sized effects of individual mutations located within a gene functionally relevant to the phenotype may range from severe disruptions of protein functioning (resulting in a Mendelian disorder) to smaller effects underlying polygenic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high heritability of intelligence, 12,28,37,38 the progress in the identification of loci consistently associated with variation in its normal range has thus far been limited. 15,17,[38][39][40][41][42] Exceptions are the apolipoprotein E (APOE) gene at older ages 43 and formin binding protein 1-like (FNBP1L), the latter having recently been shown to be associated with both childhood and adulthood intelligence. 15,17 The present approach utilizes the idea that the differentially sized effects of individual mutations located within a gene functionally relevant to the phenotype may range from severe disruptions of protein functioning (resulting in a Mendelian disorder) to smaller effects underlying polygenic variation.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In cross-sectional analyses, we found that possession of the APOE E4 allele was associated with lower verbal memory performance at age 79 years. 11 However, verbal fluency and abstract reasoning were not affected by APOE E4 carrier status.…”
Section: Introductionmentioning
confidence: 92%
“…Whereas the APOE2 protein may exert a protective effect from Alzheimer's disease, 4 the APOE4 isoform has been related to reduced neuronal survival and cognitive impairment. 5,6 Although individuals carrying at least one copy of the APOE E4 allele have an increased risk of developing Alzheimer's disease, it is less clear whether the APOE genotype may also be involved in non-pathological cognitive ageing: several studies indicate that possession of the APOE E4 allele relates to increased cognitive decline during normal ageing, [7][8][9][10][11][12][13][14] but other studies do not find evidence for such an association. [15][16][17][18] Various explanations for these conflicting results may be put forward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early imaging studies show hypometabolism in AD‐specific regions in APOE‐ε4 carriers (Reiman et al., 1996). Carriers have also shown detrimental effects on cognition in old age (Deary et al., 2002). Recent results show the correlation of APOE‐ε4 carriership with Aβ deposition, cognition, and brain atrophy (Bonham et al., 2016; ten Kate et al., 2016; Lim & Mormino, 2017).…”
Section: Introductionmentioning
confidence: 99%